306 Worse Stereotactic Radiosurgery Outcomes for Intracranial Arteriovenous Malformations After Repeat vs Initial Treatment: A Matched Cohort Study. (August 2016) - Ding, Dale; Xu, Zhiyuan; Shih, Han-Hsun; Starke, Robert M.; Yen, Chun-Po; Cohen-Inbar, Or; Sheehan, Jason P.
Abstract : INTRODUCTION: Incompletely obliterated intracranial arteriovenous malformations (AVMs) after initial treatment with stereotactic radiosurgery (SRS) can be treated with a repeat session of SRS. However, the relative efficacy of repeat vs initial SRS is not well defined. The goal of this retrospective case-control study is to compare the outcomes of repeat vs initial SRS for the treatment of matched cohorts comprising angioarchitecturally similar AVMs. METHODS: We evaluated a prospective database of AVM patients treated with SRS from 1989 to 2013. AVM patients who underwent repeat SRS with radiological follow-up of 2 years or nidus obliteration were selected for analysis and matched, in a 1:1 fashion and blinded to outcome, to previously untreated AVMs that underwent initial SRS. Statistical analyses were performed to compare the outcomes after repeat vs initial SRS. RESULTS: The matching processes yielded 84 patients in each of the repeat and initial SRS cohorts (mean margin doses 20.7 and 20.9 Gy, respectively; P = .74). In the repeat SRS cohort, obliteration was achieved in 67%; the rates of radiologic, symptomatic, and permanent radiation-induced changes (RIC) were 35%, 10%, and 4%, respectively; and the annual post-SRS hemorrhage rate was 3.1%. Compared with the initial SRS cohort, the repeat SRS cohort had significantly lower obliteration rates ( P = .038) and higher post-SRS hemorrhage rates ( P = .04). The RIC rates of the 2 cohorts were not significantly different. CONCLUSION: Repeat SRS yields considerably poorer outcomes than initial SRS for angioarchitecturally comparable AVMs. Further studies in AVM radiobiology and vascular structure are necessary to elucidate this potentially differential response.